PENGARUH LATIHAN PASSING BERPASANGAN TERHADAP KETERAMPILAN PASSING DALAM PERMAINAN SEPAK BOLA PADA SISWA SD NEGERI RENTENG - Deverance Dwi Fatriszah (Seminar Nasional Hasil Riset dan Pengabdian, 2024)
AbstractFatrsiszah, Deverance Dwi. 2024. "The Effect of Pair Passing Practice on Passing Skills in Football Games among Elementary School Students at NEGERI RENTENG". Physical Education Study Program Thesis. Faculty of Pedagogy and Psychology. PGRI Adi Buana University Surabaya.Supervisor Ismawandi Bripandika Putra, M.Pd.Keywords: pair passing, bottom passing abilityThe passes made by NEGERI RENTENG Elementary School students are still too fast and inaccurate, making it difficult for friends to receive the ball. This study aims to determine the effect of pair passing practice on the bottom passing ability of students at SD NEGERI RENTENG.This type of research is an experiment with the design "The One Group Pretest Posttest Design". The research population was 27 SD NEGERI RENTENG students. The instrument used was the low ball passing test from Subagyo Irianto (1995: 9) with a validity of 0.812 and a reliability of 0.856. Data analysis used the t test with a significance level of 5%.The results of the research show that there is a significant effect of pair passing practice on the bottom passing ability of NEGERI RENTENG Elementary School students, with a calculated t value of 6.574 > t table 2.09, and a significance value of 0.000 < 0.05, and a percentage increase of 37.69%.